Epidemiological study of ischemic heart disease in patients admitted in intensive care unit in the tertiary care hospital - Sancheti, Poonam Vijay; Mangulikar, Suresh Konappa (International Journal Of Community Medicine And Public Health, 2017)
Background: The aim of the study was to assess the epidemiological factors of ischemic heart disease in patients admitted in intensive care unit in the tertiary care hospital. Socio demographic profile of ischemic heart disease patients along with behavioral risk factors, stress factors, dietary habits and associated comorbidities were studied. Methods: Present study was carried out in patients of IHD admitted in ICU of tertiary care hospital. History about epidemiological factors was obtained from patients or relatives by separate proformas. Results: Occurrence of disease had decreasing trend with the increase in literacy status of patients, which was statistically significant at p <0.0001. Maximum patients in the study were from socioeconomic class V i.e. 144 (36.64%). Study showed that household stress was more commonly associated with occurrence of disease which was significant statistically at p <0.001. Most common behavioral risk factor seen in patients was smokeless tobacco consumption. The occurrence of ischemic heart disease was seen more in the group of patients consuming mixed diet and consuming palm oil. Most common comorbidity in patients admitted for ischemic heart disease was hypertension, which was statistically significant at p <0.001. Conclusions: Age, literacy, socioeconomic status of the patient, history of behavioral risk factors in the patient, stress and comorbidities are related to the occurrence of ischemic heart disease.